Carbonization, Hydrogenation, Oxidation and Electromagnetic Absorption of TiOx‐Pyrrole Compounds. Issue 1 (August 2017) - González‐Salgado, Francisco; Olayo, Maria Guadalupe; García‐Rosales, Genoveva; Gómez, Lidia M.; González‐Torres, Maribel; Basurto, Rafael; Cruz, Guillermo J.
Abstract : This work presents a morphologic, structural and electromagnetic absorption study in plasma‐synthesized organometallic hybrid compounds based on titanium oxide and pyrrole, which could potentially be used as photoconductive materials in solar cells. The synthesis was carried out with the combination in liquid phase of titanium tetra isopropoxide and pyrrole with 1:1 mass ratio in a glass vacuum tubular reactor with resistive electric discharges and reaction intervals from 60 to 240 min. Films and particles were formed with mean particle diameter of 438 nm. The hybrid compounds presented functional groups with multiple bonds related with pyrrole and TiOx structures. Organic and inorganic phases were detected in the hybrid matrices in which carbonization, hydrogenation, oxidation and nitridation were quantified which suggested strong dehydrogenation and the formation of multiple bonds in the plasma reactions. The compounds absorbed electromagnetic radiation in two regions with different intensity. The first and most intense one was between 190 and 350 nm wavelength, the second one was identified from 350 to 800 nm, this effect suggests that the titanium oxide is the dominant fraction in the first region and pyrrole in the second.